Novel contributions to fractional calculus: Computational methods and analysis / Mohammed K.A. Kaabar - Mohammed , K.A. Kaabar (2023)
Various computational methods are proposed and employed for solving various classes of fractional differential equations. In addition to the computational part, an analysis part is provided for some interesting research problems. First, novel exact soliton solutions of the (3 + 1)-dimensional conformable Wazwaz-Benjamin-Bona- Mahony equation are investigated via the generalized Kudryashov and exp(−